Human Fibroblast-Derived Matrix Hydrogel Accelerates Regenerative Wound Remodeling Through the Interactions with Macrophages - Savitri, Cininta; Ha Sang Su; Kwon, Jae Won; Kim, Sung Hoon; Kim, Young Min; Park, Hyun Mee; Kwon, Haejin; Ji, Mi Jung; Park, Kwideok (Wiley-VCH Verlag, 2024)
Herein, a novel extracellular matrix (ECM) hydrogel is proposed fabricated solely from decellularized, human fibroblast-derived matrix (FDM) toward advanced wound healing. This FDM-gel is physically very stable and viscoelastic, while preserving the natural ECM diversity and various bioactive factors. Subcutaneously transplanted FDM-gel provided a permissive environment for innate immune cells infiltration. Compared to collagen hydrogel, excellent wound healing indications of FDM-gel treated in the full-thickness wounds are noticed, particularly hair follicle formation via highly upregulated β-catenin. Sequential analysis of the regenerated wound tissues disclosed that FDM-gel significantly alleviated pro-inflammatory cytokine and promoted M2-like macrophages, along with significantly elevated vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF) level. A mechanistic study demonstrated that macrophages-FDM interactions through cell surface integrins α5β1 and α1β1 resulted in significant production of VEGF and bFGF, increased Akt phosphorylation, and upregulated matrix metalloproteinase-9 activity. Interestingly, blocking such interactions using specific inhibitors (ATN161 for α5β1 and obtustatin for α1β1) negatively affected those pro-healing growth factors secretion. Macrophages depletion animal model significantly attenuated the healing effect of FDM-gel. This study demonstrates that the FDM-gel is an excellent immunomodulatory material that is permissive for host cells infiltration, resorbable with time, and interactive with macrophages, where it thus enables regenerative matrix remodeling toward a complete wound healing.